How elastic is labor demand? A meta-analysis for the German labor market - Martin Popp (Journal for Labour Market Research, 2023)
The own-wage elasticity of labor demand measures the effect of higher wages on firms' demand for labor and, thus, determines the impact of supply shocks, minimum wages, and collective wage agreements on the labor market. I carry out a comprehensive meta-analysis to shed light on the nature of this parameter, leveraging 705 elasticity estimates from 105 studies on the German labor market. The average elasticity is -0.43, but entails important heterogeneity: Labor demand turns out particularly elastic for low- and high-skilled workers, in the long run, and for internationally operating firms. While empirical designs that address endogeneity deliver more negative elasticities, the analysis does not support any systematic differences by region or by margin of adjustment.
Keywords: J23; J30; D22; C83; 330; Labor demand; Wage rate; Meta-analysis; German labor market